EPIDEMIOLOGY OF OCCUPATIONAL AND NON-OCCUPATIONAL EYE INJURIES: CASES TREATED IN FOUR EYE HOSPITALS IN BANGLADESH - Md Mahmudul Hasan; Imtiaj Hossain Chowdhury; Salman Ahmed Taher Hamid; Hasnat M Alamgir; Farzanur Rahman (Global Journal of Public Health Medicine, 2023)
Introduction: Eye injury is an important cause of preventable vision loss in developing as well as developed